2020
DOI: 10.1073/pnas.2006887117
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the functional mouse CRES amyloid from globular form

Abstract: The epididymal lumen contains a complex cystatin-rich nonpathological amyloid matrix with putative roles in sperm maturation and sperm protection. Given our growing understanding for the biological function of this and other functional amyloids, the problem still remains: how functional amyloids assemble including their initial transition to early oligomeric forms. To examine this, we developed a protocol for the purification of nondenatured mouse CRES, a component of the epididymal amyloid matrix, allowing us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Diffuse rings on the diffraction pattern have been explained and described [ 48 ] in studies of non-oriented and weakly oriented amyloid samples. Similar diffuse ring reflections have been shown for amyloid aggregates of many proteins [ 10 , 40 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 76%
“…Diffuse rings on the diffraction pattern have been explained and described [ 48 ] in studies of non-oriented and weakly oriented amyloid samples. Similar diffuse ring reflections have been shown for amyloid aggregates of many proteins [ 10 , 40 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 76%
“…1 C ). This observation, however, was not unexpected based on prior CD, FTIR, X-ray crystallization, and NMR studies of the related CRES that also revealed an antiparallel β-sheet-rich structure ( 25 , 26 ).
Figure 1 CRES3 forms SDS-sensitive and SDS-resistant aggregates.
…”
Section: Resultsmentioning
confidence: 76%
“…3 B ), the outlying peaks in red boxes correspond to the conserved cystatin α-helix. The lack of helical secondary structure in the CRES3 spectrum suggests that the assembly of the CRES3 amyloid involves a transition of α-helix to β-strand, similar to conformational changes observed in the polymerization of other amyloids including CRES ( 26 ). We confirmed that this is a likely possibility by repeating this exercise using our β-sheet and turn only CRES3 model ( Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations